(untitled) (Research, Society and Development, 2022)
This paper aims to analyze the contributions of being a monitor in the Health and Citizenship discipline in the academic training of future health professionals. The bibliographic research method was used in electronic databases Scielo, Google Scholar and the Virtual Health Library (VHL) for a theoretical foundation on the subject. The research database consisted of two stages, first the analysis of the reports of the monitors of the referred discipline from the years 2015 and 2016 of the Faculty of Health Sciences of Trairi (FACISA/UFRN), second the realization of 4 Focus Groups among the months of May and June 2016, consisting of 6 students each. The focus groups were recorded and transcribed in full, resulting in a database submitted for analysis in the IRAMUTEQ Software. The exploration of the records of the reports of the SACI monitors allowed the construction of a category called "Contributions to academic training through the experience in monitoring SACI". The material obtained by the focus groups provided the formation of three thematic categories, namely: Understanding of the SACI discipline; Experience in the social environment and health services and (re)learning in everyday life. The structural pillars of all universities are: teaching, research and extension. teaching-learning in graduation through mutual cooperation between monitor student, teacher and target students of monitoring, in addition to acting as a stimulus for initiation to teaching and for its appreciation.